Changes in the cortical bone reaction around the stem after uncemented total hip replacement using short tapered wedge stem - Hao Dinh Anh Hoang; Hironobu Hoshino; Mitsuru Hanada; Yukihiro Matsuyama (Journal of Joint Surgery and Research)
Purpose: This study examined the relationship between stem alignment and the cortical bone area around the distal end of the femoral component using three-dimensional computed tomography (3D-CT) images after uncemented total hip arthroplasty (THA). Methods: A total of 59 patients who underwent primary THA using an uncemented short tapered wedge stem from 2019 to 2021 were followed for at least 24 months. Patients were divided into groups based on stem position. Changes in stem position and cross-sectional area of femoral cortical bone at the distal end of the stem were examined using 3D-CT at 12 months and 24 months post-operatively and were compared with pre-operative values. Results: The 12-month post-operative cortical bone area around the stem showed significant differences compared with the pre-operative area in the anterior, posterior, and lateral zone 1. Differences at these same points were noted when comparing the 24-month post-operative area with the pre-operative area. No significant difference was found in the change in the cortical bone area over time among the neutral, flexed, and extended stem groups. In the varus stem group, a significant increase in cortical bone area over time was observed in lateral zone 2. In the valgus stem group, a significant increase in the cortical bone area over time was observed in medial zone 1. Conclusions: Stem alignment may affect periprosthetic cortical bone changes after THA using an uncemented short tapered wedge stem. Cortical bone reaction was revealed laterally to the stem tip in the varus-aligned stem, and medially to the stem tip in the valgus-aligned stem.